CRITICAL REVIEW (Editora Impacto Científico, 2025)
The book “Inclusão escolar: o que é? por quê? como fazer?”, by Maria Teresa Eglér Mantoan (2003), is a fundamental work for the debate on inclusion in education. The author criticizes the traditional and segregated view of education, proposing a new paradigm that values the diversity and singularities of students. Mantoan conceptualizes inclusion as a structural and cultural change in the school, which goes beyond the simple inclusion of students in the regular classroom, advocating curricular flexibility and democratic pedagogical practices. The book highlights three pillars justifying inclusion: identity and difference, the legal guarantee and the need for change in the face of educational challenges. It also emphasizes that building an inclusive school depends on the involvement of the entire school community and overcoming social and political obstacles. Finally, it proposes an active, dialogical and humanizing pedagogy, based on respect for differences, the promotion of autonomy and citizen training, contributing to a fairer and more equitable education.